Numerical Analysis of Short Pulse Optical Parametric Amplification Using Type I Phase Matching - Dement’ev, A.; Vrublevskaja, O.; Girdauskas, V.; Kazragytė, R. (Nonlinear Analysis: Modelling and Control, 2004)
The possibilities of efficient amplification and additional shortening of faster moving short fundamental harmonic pulses by the more slowly moving longer second harmonic pulses for type I phase matching are numerically analyzed for initially collimated axially symmetric beams, taking into account diffraction, group velocity mismatch and dispersion of the pulses.